Formulasi Dan Evaluasi Sediaan Tablet Ibuprofen Menggunakan Berbagai Bahan Pengikat Dalam Metode Granulasi Basah - Nor Aida; Nafach Olya Warasky; Laila manada; Annur tasya alfiati; Sofi agustia putri (CV. ITTC INDONESIA, 2024)
The aim of this research is to conduct a study on the Formulation and Evaluation of Ibuprofen Tablet Preparations Using Various Binder Materials in the Wet Granulation Method. The method used in this research is a systematic literature review. The results of this study indicate that research on ibuprofen tablet formulations shows that the physical quality of tablets is greatly influenced by the selection of binders, disintegrants, lubricants, and other excipients. The appropriate binder ensures that the tablet has the correct hardness and can disintegrate properly, allowing the active ingredient to be effectively absorbed by the body. The right disintegrant is also crucial for speeding up the tablet's disintegration time, while the lubricant functions to reduce friction during tablet manufacturing, although it must be used in a balanced amount to avoid hindering dissolution. Furthermore, factors such as the moisture content of the granules and the physical properties of the granules also play a role in determining the tablet's quality. Studies show that the right formulation, such as a combination of CMC-Na, sorbitol, and amylum solani binders, can improve dissolution and bioavailability, leading to better therapeutic effectiveness. Overall, the selection of the appropriate materials and proportions in the formulation of ibuprofen tablets is crucial to produce tablets with high bioavailability and optimal therapeutic effects..